Copper Oxide Nanoparticles in Agri-Nanotechnology : Green Synthesis, Pathogen Targeting, and Regulatory Outlook (International Journal of Scientific Research in Science and Technology, 2025)
The increasing demand for eco-friendly and sustainable agricultural practices has driven interest in nanotechnology-based solutions, notably copper oxide nanoparticles (CuO NPs). This review comprehensively explores the plant-mediated synthesis, characterization, antimicrobial activity, and regulatory perspectives of CuO NPs with specific emphasis on their potential against phytopathogens. Green synthesis using medicinal and crop plant extracts offers a cost-effective and environmentally benign alternative to traditional chemical and physical methods, leveraging phytochemicals such as flavonoids, polyphenols, and alkaloids for reduction and stabilization. Characterization techniques including SEM, TEM, XRD, FTIR, UV-Vis, and DLS confirm the nanoparticles’ nanoscale morphology, crystallinity, and functional properties. CuO NPs demonstrate significant antimicrobial effects through disruption of microbial membranes and generation of reactive oxygen species (ROS), leading to DNA damage, enzymatic inhibition, and apoptosis in phytopathogens. In vitro evaluations using disc and well diffusion assays, and in vivo assessments in greenhouse and field trials, validate their effectiveness in managing diseases caused by Fusarium, Xanthomonas, and Botrytis species. Furthermore, CuO NPs may act as plant immunity stimulants by enhancing the expression of pathogenesis-related (PR) proteins and secondary metabolites. However, cytotoxicity and phytotoxicity studies reveal potential adverse effects on non-target plant species and beneficial soil microbiota, highlighting the need for precise dosing and risk evaluation. Regulatory frameworks by the EPA, EU, and Indian agencies remain fragmented, necessitating harmonized global standards. Future directions include smart nanobiotechnology integration through synergistic formulations with ZnO and Ag NPs, development of seed coatings and foliar sprays, and scalable green synthesis. Addressing challenges in commercial-scale production, cost-effectiveness, and safe disposal will be pivotal for mainstream agricultural adoption.